Green technology purification of natural gas via Co2/H2 methanation by using trimetallic Ru/Mn/Fe-Al2O3 oxide catalyst - Ab. Halim, Ahmad Zamani (2013)
The presence high content of carbon dioxide (CO2) and hydrogen sulphide (H2S) in crude natural gas which can block cryogenic equipments and favours steel-pipes corrosion thus will decrease the quality of the natural gas. Therefore, there is need to treat sour to sweet natural gas by using green technology via catalytic methanation reaction by converting CO2 to methane gas. Using waste to wealth concept, production of methane would increase as well as creating environmental friendly approach for purification of natural gas. In this work, the investigations of new trimetallic Ru/Mn/Fe-Al2O3 oxide catalysts were conducted and the catalysts were prepared by wet impregnation method. The catalysts were activated at different temperatures (100-1100°C) for 5 hours and at different ratios of metal. The additions of Ru into catalysts had improved the CO2 conversion and CH4 formation compared with the undoped. Ru/Mn/Fe (5:35:60)/Al2O3 catalyst calcined at 1000°C was assigned as the most potential catalyst, which gave 96.1% CO2 conversion at reaction temperature of 270°C. Moreover, the XRD diffractograms showed that the catalyst calcined at high temperature were highly crystalline phase while, catalysts calcined at low temperature showed highly amorphous in structure which was dominated by Al2O3 support material. The FESEM analysis revealed that fresh and used catalyst were covered with homogeneously dispersed and small size surface particles in the range of 0.2-0.4 μm. Nitrogen adsorption analysis showed, the surface area increased from single to bimetallic and trimetallic catalyst.